Monitoring Arus dan Tegangan Pembangkit Listrik Tenaga Surya Menggunakan Internet Off Things - Yosi Apriani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The application of Solar Power Plant (PLTS) technology to utilize the available solar energy potential is the right solution in reducing dependence on PLN energy providers. However, some PLTS are not equipped with current and voltage monitoring tools, including the PLTS at the LKC Dompet Duaffa clinic in Palembang which is not equipped with current and voltage monitoring tools. When the inverter works, the battery should be separated from the inverter, this is intended to prevent the battery from over-discharge because the output power of the inverter when on grid will work at its maximum Therefore, developing a current and voltage monitoring system using the Internet of Things (IoT) so that it can be monitored remotely and will regulate the charging and discharging mechanism of the battery in the PLTS configuration, so that the continuity of inverter operation can be maintained in supplying loads.